Auditorío del rubro costos de productos vendidos del restaurante de un hotel, en la ciudad de Guayaquil, por el período terminado al 31 de diciembre del 2008 - Fernández Carrión, Jennifer Andrea (2010)
The present project presents a Financial Audit to the sold products Costs area of the Restaurant of a hotel in the City of Guayaquil, by the period finidhed to December 31, 2008, having as main objetive to verify the reasonableness of its balance